ENT600 : Ramly Halal Mart / Ku Nazirah Ku Aziz ... [et al.] - Ku Aziz, Ku Nazirah; Mior Ahmad Faizal, Mior Afiq Hilmi; Hasim, Fatin Syahirah; Moden, Abdul Niat; Shukri, Siti Natasha (2019)
Ramly Halal Man has been recognized by all people around Seksyen 2 or UiTM students. Ramly Burger was established in the year of 2014 which managed by En. Shamsul Zairee. This company was provided two sections in their business which was frozen food and fast food selling. Ramly Halal Mart was currently stands as one of the biggest Ramly Burger in Shah Alam area. This, company leads with sales of RM 4000+- per day. Although the company has quite high number of sales, but their sales majority got from frozen food or supply products. They were got low profits according to their restaurant sales. Based on analysis, low profits from restaurant sales due to the facts of higher price of fast food plus there were food courts in front of their premise. Hence, for sure people will go and buy foods with lower prices. Therefore, Ramly Halal Mart was makes another strategies which upgrade their menu in their restaurant to gain more profits.